Ultrafast temporal evolution of interatomic Coulombic decay in NeKr dimers. Issue 6 (26th January 2022) - Trinter, F.; Miteva, T.; Weller, M.; Hartung, A.; Richter, M.; Williams, J. B.; Gatton, A.; Gaire, B.; Sartor, J.; Landers, A. L.; Berry, B.; Ben-Itzhak, I.; et al.
Abstract : We investigate the time-resolved dynamics of interatomic Coulombic decay in NeKr dimers after neon inner-valence photoionization using a synchrotron light source. Abstract : We investigate interatomic Coulombic decay in NeKr dimers after neon inner-valence photoionization [Ne + (2s −1 )] using a synchrotron light source. We measure with high energy resolution the two singly charged ions of the Coulomb-exploding dimer dication and the photoelectron in coincidence. By carefully tracing the post-collision interaction between the photoelectron and the emitted ICD electron we are able to probe the temporal evolution of the state as it decays. Although the ionizing light pulses are 80 picoseconds long, we determine the lifetime of the intermediate dimer cation state and visualize the contraction of the nuclear structure on the femtosecond time scale.